Processes regulating groundwater chloride content in marshes under different environmental conditions: A comparative case study in Península Valdés and Samborombón Bay, Argentina - Carol, Eleonora Silvina (2016)
Salt marshes are some of the most important wetlands in many regions of the world. Soil and groundwater salinity plays an important role in coastal wetland ecosystems because of the differences in tolerances of plant species to salinity and tidal inundation. Given that the salinity of these environments is mostly dominated by the chloride anion, it is the aim of this study to identify the geochemical processes that regulate its content in groundwater. A comparison of two intertidal wetlands under different environmental conditions was carried out in Peninsula Valdés and in Samborombón Bay, both on the Atlantic coast of Argentina. The tidal influence over the groundwater marsh dynamics was analyzed from continuous records of groundwater levels and electrical conductivity. Besides, major ion and environmental isotope data were used to identify the geochemical processes that determine the chloride content, based on the study of ion ratios and analytical models. The results show that, despite the hydrological differences between the two studied marshes, the processes regulating the Cl− contents are similar: evaporation, transpiration and halite dissolution. Among them, evaporation/transpiration are the processes that could continuously increase the chloride concentration. However, it is expected that those are not processes that greatly increase the groundwater saline content if compared to the dissolution of halite.